MiR‐15a‐5p suppresses inflammation and fibrosis of peritoneal mesothelial cells induced by peritoneal dialysis via targeting VEGFA. Issue 6 (26th October 2018) - Shang, Jin; He, Qianxin; Chen, Ying; Yu, Dahai; Sun, Lulu; Cheng, Genyang; Liu, Dong; Xiao, Jing; Zhao, Zhanzheng
Abstract: Long‐term peritoneal dialysis (PD) often ends up with ultrafiltration failure (UFF) which is partially caused by persistent inflammation and fibrosis of peritoneal tissues. However, the mechanism is still unclear. In the current study, the peritoneum from UFF patients demonstrated inflammation and fibrosis which were positively related to the expression of vascular endothelial growth factor A (VEGFA). The in vitro model using human peritoneal mesothelial cells (HPMCs) stimulated by high glucose or advanced glycation end (AGE) product showed consistent changes of inflammation, fibrosis, and VEGFA. What's more, we showed that VEGFA was an instigator of inflammation and fibrosis. Several microRNAs (miRNAs) have been reported to regulate expression of VEGFA elsewhere. Five of them were selected to test the expression in the peritoneum of patients with PD. Results suggested that miR‐15a‐5p was the most significantly downregulated one. Also, in high glucose or AGE product‐stimulated HPMCs, miR‐15a‐5p decreased. When miRNA mimic was used to restore the expression of miR‐15a‐5p, high glucose‐induced VEGFA was repressed. The predicted binding site between these two molecules was confirmed by the dual‐luciferase assay. Restoration of miR‐15a‐5p restrained inflammation and fibrosis of HPMCs. TGF‐β1/Smad2 was shown to be the downstream signaling pathway and their activity was regulated by miR‐15a‐5p/VEGFA. In conclusion, our current study demonstrates that miR‐15a‐5p acts as a regulator of VEGFA mRNA and the following inflammation and fibrosis in peritoneal mesothelial cells. The miR‐15a‐5p/VEGFA pathway may be a potential target for preventing ultrafiltration failure in patients with PD. Abstract : Our current study demonstrates that miR‐15a‐5p acts as a regulator of vascular endothelial growth factor A messenger RNA (VEGFA mRNA) and the following inflammation and fibrosis in peritoneal mesothelial cells. The miR‐15a‐5p/VEGFA pathway may be a potential target for preventing ultrafiltration failure in patients with peritoneal dialysis .